Bis(pyridylimino)isoindolato-iridium complexes as epoxidation catalysts for alkenes - Camerano, José A.; Sämann, Christoph; Wadepohl, Hubert; Gade, Lutz H. (Organometallics, 2011)
The reaction of the sodium salts of ligands 1a,b (1a = 1,3-bis(2-(5-(3,5-xylyl)pyridyl)imino)-5,6-dimethylisoindole, 1b = 1,3-bis(2-(4-tert-butylpyridyl)imino)-5,6-dimethylisoindole) with [Ir(μ-Cl)(COD)]2 (COD = cyclooctadiene) and [Ir(μ-Cl)(C2H4)2]2 afforded the corresponding isoindolato complexes [{BPI(1a,b)}IrI(COD)] (2a,b) and [{BPI(1a,b)}IrI(C2H4)2] (3a,b), respectively. The catalytic activity of the complexes 2a,b was tested in the epoxidation of a wide range of non-electron-rich olefins, using PPO (PPO = 3-phenyl-2-(phenylsulfonyl)-1,2-oxaziridine) as oxidizing agent, giving the corresponding epoxides in moderate to high yields.
Gesehen am 27.06.2022